Effect of Copper and Manganese Ions on Activities of Laccase and Peroxidases in Three Pleurotus Species Grown on Agricultural Wastes - Mirjana Stajic; Limor Persky; Yitzhak Hadar; Dana Friesem; Sonja Duletic-Lausevic; Solomon P. Wasser; Eviatar Nevo
Copper (Cu2+)and manganese (Mn2+)ions influenced laccase (Lac)and peroxidase production in Pleurotus eryngii, Pleurotus ostreatus, and Pleurotus pulmonarius. In P. eryngii, the optimum Cu2+ concentration for Lac production was 1 mM and for peroxidases 10 mM, and Mn2+ concentration of 5 mM led to peaks of Lac and peroxidase activity. In P. ostreatus HAI 493, the highest level of Lac activity was at Cu2+ concentrations of 1 and 10 mM and Mn2+ concentration of 1 mM, respectively. The absence of Cu2+ and Mn2+ caused the highest levels of peroxidase production. In P. ostreatus HAI 494, the highest level of Lac activity was at a Cu2+ concentration of 5 mM and at Mn2+ concentration of 1 mM, respectively. High levels of peroxidase activity were found in the medium without and with 1 mM Cu2+, and at 1 and 5 mM Mn2+, respectively. In P. pulmonarius, the highest Lac activity was found in the presence of 5 mM Cu2+ and 5 mM Mn2+, respectively. The absence of Cu2+ and Mn2+ as well as their presence at a concentration of 1 mM led to the peaks of peroxidase activities.
Keywords: PLEUROTUS ERYNGII; PLEUROTUS OSTREATUS; PLEUROTUS PULMONARIUS; LACCASE; PEROXIDASES; COPPER; MANGANESE